The internet usage behaviour among SME’s in Melaka / Hamirah Ab Rahim and Siti Nor Zilah Ramli - Ab Rahim, Hamirah; Ramli, Siti Nor Zilah (Faculty of Business and Management, 2013)
The purpose of this research is to identify the internet usage behaviour among the SME’s in Melaka. There are three factors that will determine the internet usage behaviour among the SME businesses that are the organization readiness, external pressure and perceived benefits which are the independent variables for this research. The research is being conducted towards the SME’s customers of Telekom Malaysia Berhad in Melaka, and more focuses on three areas that are in Bukit Beruang, Ayer Keroh and Melaka Raya. The information is gathered by distributed questionnaire to the SME’s businesses by using the simple random sampling, that there are 120 respondents from the three selected area. But only 80 respondents selected for the research that 27 respondents from area of Bukit Beruang, 27 respondents from area Ayer Keroh and another 26 respondents are from Melaka Raya. Their feedbacks on answering the questionnaire will be analyze and summarize by using The Statistical Package for Social Science (SPSS) version 19 and above. The results or the findings from this research revealed that only perceived benefits factors will effects the SME’s in Melaka used the internet in their business operations. Thus, several suggestions and recommendations are being made in order to encourage the SME’s in Melaka to use internet for the business operation purposes.